Developing Higher Education Curricula for Undergraduate Programs in Libyan Universities (Applied Sciences): A Critical Analytical Study of Challenges and Modern Mechanisms in Light of Contemporary Requirements (Sebha University Conference Proceedings, 2025)
The aim of this study was to analyze the higher education curricula for the undergraduate stage in Libyan universities, specifically in "applied sciences," and to provide proposals for their development in alignment with the requirements of the digital age and the labor market. The study utilized the tool of analyzing previous studies, based on a comprehensive academic review of scientific research, theses, and peer-reviewed articles. The study followed a qualitative descriptive analytical approach (theoretical library study), where existing literature and previous studies in this field were gathered and analyzed. The importance of this study lies in providing an in-depth analysis of higher education curricula in the Arab region, which may contribute to offering solutions to the challenges faced in developing academic curricula. The study also helps in identifying modern mechanisms that can contribute to updating curricula to match technological advancements and the growing needs of the labor marketThe study concluded that current curricula suffer from deficiencies in meeting the needs of the labor market, especially in the fields of technology and innovation. Additionally, it was found that the process of curriculum development faces significant challenges, such as the gap between theoretical education and practical application, reliance on traditional teaching methods, and limited financial resources. Furthermore, universities face difficulties in updating curricula due to a lack of specialized training for faculty members. The study recommended the integration of technology in e-learning and blended learning, the application of project-based learning to bridge the gap between theoretical knowledge and practical application, and the continuous assessment of curricula to ensure their alignment with technological developments and labor market needs, with an emphasis on enhancing faculty training in modern teaching methods.